THE USE OF THE ATUMICS METHOD FOR THE DEVELOPMENT OF DESIGNS FOR WOMEN'S LEATHER BAGS - Fernanda , Daffa Afisona; Jakaria , Ribangun Bamban (Journal for Technology and Science, 2024)
Abstract: Leather bags are popular consumer products, frequently undergoing innovations to meet evolving aesthetic preferences and market demands. While leather artisans continuously experiment with new designs, integrating traditional and contemporary styles remains an underexplored area, especially in the application of batik printing on leather. To address this knowledge gap, this study seeks to enhance leather bag designs by incorporating batik printing, aiming to modernize traditional motifs and elevate the cultural value of these products. Using the ATUMICS method—a structured approach that harmonizes traditional and modern elements through Artifact, Technique, Utility, Material, Icon, Concept, and Shape criteria— the study examined the impact of adding batik printing designs on the feasibility and consumer appeal of leather bags. Findings reveal that leather bags with batik printing achieve higher feasibility scores, with product evaluations improving from 30–65% to 80–100% after applying the ATUMICS method, based on a questionnaire completed by ten experienced artisans. Validity and reliability tests yielded values (validity: 0.716–0.967; reliability: Cronbach's Alpha 0.885) that confirm the robustness of the instrument used. The novelty of this research lies in demonstrating the potential of batik-printed leather bags as a culturally resonant, modern product for broader markets. Implications suggest that integrating traditional patterns with contemporary aesthetics can revitalize interest in leather crafts and serve as a model for other traditional crafts, providing artisans with valuable insights into product differentiation and market adaptation. Future research should expand on design variations in form and color to further enhance the diversity of leather bag offerings and maintain the cultural significance of traditional art forms in modern fashion.